Pengendalian Mobile Robot Berbasis Webcam Menggunakan Perintah Isyarat Tangan - Richard Andriessen, Daniel; Harianto, Harianto; Christrian W., Madha (Journal JCONES, 2012)
Robotino isan Omni-Directional robot created by Festo Didatic that already integrated webcam with a USB interface and a system using omni-directional movement of the drive is capable of moving in all directions and has a variety of sensors that can be programmed as needed. It background in the development of controlrobot technology, the research is “application mobile robot control webcam-based using a hand gesture commands”, which uses image processing template matching methods. Robotino can do the movement in accordance with the detected hand gesture commands from the camera on the Personal Computer (PC) which integrated with Robotino. The application can detect this type of human hand gesture commands using HSV color space with 100% success rate of 20 times the distance between the test by making a hand gesture with a PC camera between 110 up to 130 cm. Keywords: Robotino, HSV Color Filtering, Metode Template Matching